ANALISIS PENDAPATAN ASLI DAERAH, DANA BAGI HASIL DAN DANA ALOKASI UMUM TERHADAP ANGGARAN BELANJA MODAL - Wahyuni, Endang Sri; Rosmida, Rosmida (Komunitas Manajemen Kompetitif, 2018)
Abstract: This study aims to determine the effect of Local Own Revenue, Revenue Sharing, General Allocation Funds, affect the Capital Expenditure Budget District / City Government on the island of Sumatera. The population in this study is the district/city governments in Sumatra. By using purposive sampling method, of 151 regencies / cities in Sumatra obtained a sample of 122 district / city. This research is a quantitative research using secondary data. Testing the hypothesis in this study using multiple linear regression with t test, and the coefficient of determination. The results showed that the Local Own Revenue, Revenue Sharing, General Allocation Funds significant affect Budget Capital Expenditure.